Makna Logo Depok Friendly City (Analisis Semiotika Charles Sanders Peirce Pada Logo Depok Friendly City sebagai City Branding Kota Depok) - Sultan Kemal Piagio; Hanny Hafiar; FX. Ari Agung Prastowo (Universitas Merdeka Malang, 2022)
As a metropolitan city, Depok City strives to improve the comfort of its city in accordance with its new nickname, a friendly city. This study aims to determine the symbols, meanings, and how the symbols contained in the “Depok Friendy City” logo could construct the “city branding” of Depok City as a “friendly city”. This study used a qualitative method with Charles Sanders Perice's semiotic analysis. The data collection techniques used were media text analysis, interview, documentation, and literature study. The results of this study indicate that there is a value to be given to the community, it is Depok as a “Friendly City